Determinants of Members’ Loyalty in Cooperative Housing Societies in Lahore - Rehman, Munib ur; Awan, Farrukh Ahmad (Green Publisher Indonesia, 2023)
This is going to be first ever study that aims to explore phenomenon of loyalty of members in Cooperatives in Pakistan. Cooperatives are unique enterprises in terms of their business model, working on the seven principles of Cooperatives. Members’ participation is the significant element in the functioning of a Cooperatives and this model is getting attention in the emerging economies around the globe. In Pakistan, especially in the Province of the Punjab, 33000+ Cooperative organizations, 255 out of which are Cooperative Housing Societies, play a vital role in different areas of life. In order to ascertain the inclination of the members, who are also consumers in management terms, towards cooperatives, 03 Cooperative Housing Coops i.e. The Cooperative Model Town Society Ltd. Lahore, The State Enterprise Cooperative Housing Society Ltd. Lahore and PASCO Employees Cooperative Housing Society Ltd. Lahore were chosen as research site. Four Proposition i.e Satisfaction, Perceived value, Response to change, and trust were formed and were looked into so as to assess their role on loyalty. Hence, a qualitative approach was adopted. Thematic Analysis was carried out on the data/information retrieved through interviews. It was observed that that perceived value, resistance to change and trust have been treated as important towards members’ loyalty. However, proposition of satisfaction was given little significance. This study gives a future direction of the research in Cooperatives besides providing an insight into managerial implications of the Cooperative Organizations as service providers as well as of cooperative members.